Implementasi Pendekatan Seni Kolase Dalam Menstimulasi Keterampilan Abad Ke-21 pada Anak Usia Dini - Ni Wayan Ria Lestari; Ida Ayu Made Yuni Andari (Widya Sundaram : Jurnal Pendidikan Seni Dan Budaya, 2023)
Developing children's 21st century skills through an arts approach is a creative and effective way to broaden horizons and experiences. Art can involve visuals, music, dance, theatre and various forms of creative expression. This study aims to analyse the collage art approach in stimulating 21st century skills at the kindergarten level. In this study using a field research method with a descriptive analysis qualitative approach. The results found in this study are 1). Visual communication skills, Collaboration, Building critical skills, Technology skills, Multidisciplinary skills, Social and emotional skills development. 2). The implications are creativity and innovation, problem solving and critical thinking, collaboration and communication, technological skills in the digital era, multidisciplinary understanding, Improved social and emotional skills. 3). The obstacles are limited resources, lack of time, lack of teacher knowledge and skills, and challenges in proper assessment.